Мечі та кинджали у поховальному обряді Усть-Альмінського некрополя - Медведєв, Г.В. (Археологія і давня історія України, 2020)
У статті розглянуто поховання з мечами та кинджалами з Усть-Альмінського пізньоскіфського некрополя, визначено їх типи, кількість та хронологію, а також роль клинкової зброї у поховальному обряді — функціональну та як соціальний індикатор. На Усть-Альмінському некрополі з’являються традиції поховального обряду, характерні для населення сарматської доби, через контакти із степовими In terms of the number of weapons the Ust-Alma necropolis stands out among the Late Scythian sites of the Crimea. The paper deals with burials accompanied by swords and daggers. Their types, quantity and chronology are defined in the paper. The main role of the bladed weapons in the funeral rite played its functional purpose but besides this it could have the sacred meaning or play the role of the social indicator in the military elite, female and children burials. The analysis of the burial assemblages showed that the large role in the burial rite of the Ust-Alma necropolis was played by bladed weapons. From the mid-1st century AD. the number of bladed weapons in the burial assemblages of Ust-Alma necropolis increased. In the 1st century AD. Chersonesos and most of the Crimea (including the Late Scythian state) were controlled by the Bosporan kingdom. Crimean Scythia participated in the Roman-Bosporan war as the ally of Bosporus. In the 2nd century AD. the military actions of the Bosporan army also took place on the territory of the Crimean Scythia. This phenomena was reflected in the funeral rite. In the first centuries AD. the traditions of the funeral rite characteristic for the Sarmatian Age population of the steppe regions of Northern Pontic area and the Volga region have appeared at the necropolis. This was reflected in a number of single but special features of the rite. In addition, there are changes in the ethnic and social structures of the population of the Ust-Alma Late Scythian settlement. Together with the public elite, the military one had formed whom graves are distinguished by rich grave goods (precious metal, bronze dishes, amphorae, horse bridle). The funeral rite of the Ust-Alma necropolis has many similarities with the funeral rite of the Sarmatians in the Don and Kuban regions and the Asian Bosporus.